Sharing the genetic diversity of solanaceous food crops. Project profile. - International Potato Center (International Potato Center, 2019)
Potato, tomato, pepper, and eggplant or aubergine are key food security and commercial crops. Making their genetic diversity more widely available will support the livelihoods of farmers and other enterprises around the world. This project aims to streamline access to the extensive genetic resources of these crops.